THE INFLUENCE OF ONLINE ENTREPRENEURSHIP TRAINING ON STUDENT ENTREPRENEURIAL INTEREST IN BATAM CITY - Putra, Rio; Heru Wijayanto Aripradono (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Entrepreneurial interest is one of the important aspects of developing the entrepreneurial spirit in students. However, not all students have sufficient interest or skills to engage in entrepreneurial activities. Therefore, this study aims to explore efforts to increase students' entrepreneurial interest through online entrepreneurship training. This study used qualitative research methods. The data collection technique was carried out by a literature study. The data that has been collected is then analyzed using thematic analysis. The results show that entrepreneurship training helps foster entrepreneurial interest by providing knowledge, skills, inspiration, and a supportive environment to start and develop a business. With effective entrepreneurship training, it is expected that participants' interest in entrepreneurship will increase and encourage them to embark on an entrepreneurial journey with confidence and success. When students have a high interest in entrepreneurship, they tend to have a strong motivation to learn and develop the skills needed in the business world. High interest can also trigger creativity, the desire to create new solutions, and perseverance in facing the challenges that exist in the entrepreneurial world.